Optimization the Role of Shariah Supervisory Board for Shariah Governance in Islamic Banking - Izzani Ulfi; Ujang Syahrul Mubarrok; Muhamad Wahyudi (Perisai : Islamic Banking and Finance Journal, 2020)
Many studies show that one of the biggest challenges in Islamic banking is related to lack of proper and effective Shariah governance. By focusing on the role of Shariah Supervisory Board (SSB), this paper attempts to extract some keys on how to achieve better performance and development of Islamic banking industry by reviewing previous studies. This study was done by using literature review approach. This study concludes that increasing the size of SSB, improving higher skills and competences of SSB members, keeping the independency of SSB member as well as the need of Central Shariah Board (CSB) and shariah auditor would affect to better performance of Islamic banking.